Body Mass Index and the Association With Vaso-occlusive Crises in Pediatric Sickle Cell Disease. Issue 4 (May 2017) - Zivot, Andrea; Apollonsky, Nataly; Gracely, Edward; Raybagkar, Deepti
Abstract : Background: Children with sickle cell disease (SCD) historically have been underweight and have poor overall growth. Recent studies have demonstrated a trend toward obesity in pediatric SCD populations. Materials and Methods: Through retrospective chart review of patients with SCD followed at our center, we collected patient's data, including body mass index (BMI), weight percentiles, sickle cell genotype, baseline hemoglobin, medical and psychiatric comorbidities, 25-hydroxy vitamin D level, treatment with hydroxyurea, and chronic transfusions. We identified hospitalizations to St. Christopher's Hospital for vaso-occlusive crisis (VOC) and duration of hospitalization and intravenous opioid use were recorded. Student t test, Mann-Whitney U test, and analysis of variance were used to examine associations between variables and frequency and duration of hospitalizations for VOC. Results: Among 328 patients with SCD, overweight and obese children constituted 19% of hospitalized and nonhospitalized patients. BMI status did not influence frequency ( P =0.90) or duration of hospitalization ( P =0.65) for VOC. Obesity was more associated with HbSC than HbSS ( P =0.025) genotype. Conclusions: Our study did not demonstrate an association between extremes of BMI of patients and hospitalization for VOC. Considering current trend toward obesity, further prospective and interventional research are required to define the effects of extremes of BMI on pain crises in SCD.